Influence of size effects and granule distribution by size on optical and magneto-optical properties of nanocomposites - A. N. Yurasov; M. M. Yashin; I. V. Gladyshev; D. V. Semyonova; E. A. Gan’shina; E. S. Kanazakova (Российский технологический журнал)
In this paper, the spectral dependences of the transverse Kerr effect (ТКЕ) are studied experimentally and theoretically. The results are obtained for deposited and annealed samples with a corresponding variation in the size of the granules. It was found that thermomagnetic annealing leads to an increase in the ТКЕ value in magnetic nanostructures, while the most noticeable changes in the effect value were observed in the range of medium and high concentrations of the magnetic component in the visible region of the spectrum. The expediency of using the effective medium approach for calculating magneto-optical effects in granular systems, taking into account the size distribution of granules within the lognormal distribution of granules, is shown. Based on this approach, the main features of the optical and magneto-optical properties of nanocomposites are explained by the example of (Co45Fe45Zr10)X(Al2O3)1–X. All calculations are performed in the Bruggemann approximation, which effectively describes the properties of nanostructures in the region of average concentrations. Size effects are clearly manifested in nanocomposites and have a significant impact on the optical and magneto-optical properties of nanocomposites, especially in the IR region of the spectrum, which is associated with intraband transitions. Taking into account the particle size distribution makes it possible to significantly improve the description of such promising inhomogeneous nanostructures. The solved problem is very important and relevant both from the fundamental point of view – the study of magneto-optical, optical and transport phenomena in nanocomposites – and from the point of view of the great possibilities of their application in modern electronics and nanoelectronics. Taking into account the size effects and the particle size dispersion makes it possible to find new promising functional materials and control their properties in a wide spectral range.